MARITIME SUPPLY CHAIN RISKS ANALYSIS OF THE INDONESIAN SHIPBUILDING INDUSTRY - Putri Rahmatul Isti'anah (Proceeding Maritime Business Management Conference, 2024)
In the face of volatile market demand, the shipbuilding industry must focus on enhancing its growth and productivity to ensure its survival, especially in the aftermath of the pandemic. The ETO business model adopted by Indonesian shipyards is complex and vulnerable, necessitating a clear understanding of customer requirements within the ship construction and repair services market. Moreover, addressing the dynamic risks present in the maritime supply chain is crucial. Identifying effective mitigation strategies requires shipyards to understand the common threats they face comprehensively. To facilitate this, this study employs the House of Quality (HOQ) tool within the Quality Function Deployment (QFD) methodology to analyse the needs of customers and maritime supply chain risks in the shipbuilding sector, aiming to secure their sustainability over the long term.